Carbon Catabolite Repression Regulates the Production of the Unique Volatile Sodorifen of Serratia plymuthica 4Rx13 - Magnus, Nancy; Weise, Teresa; Piechulla, Birgit (Frontiers in Microbiology, 2017)
Microorganisms are capable of synthesizing a plethora of secondary metabolites including the long-overlooked volatile organic compounds. Little knowledge has been accumulated regarding the regulation of the biosynthesis of such mVOCs. The emission of the unique compound sodorifen of Serratia plymuthica isolates was significantly reduced in minimal medium with glucose, while succinate elevated sodorifen release. The hypothesis of carbon catabolite repression (CCR) acting as a major control entity on the synthesis of mVOCs was proven by genetic evidence. Central components of the typical CCR of Gram-negative bacteria such as the adenylate cyclase (CYA), the cAMP binding receptor protein (CRP), and the catabolite responsive element (CRE) were removed by insertional mutagenesis. CYA, CRP, CRE1 mutants revealed a lower sodorifen release. Moreover, the emission potential of other S. plymuthica isolates was also evaluated.